2014
DOI: 10.1002/mbo3.174
|View full text |Cite
|
Sign up to set email alerts
|

Cuticles of European and American lobsters harbor diverse bacterial species and differ in disease susceptibility

Abstract: Diseases of lobster shells have a significant impact on fishing industries but the risk of disease transmission between different lobster species has yet to be properly investigated. This study compared bacterial biofilm communities from American (Homarus americanus) and European lobsters (H. gammarus), to assess both healthy cuticle and diseased cuticle during lesion formation. Culture-independent molecular techniques revealed diversity in the bacterial communities of cuticle biofilms both within and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
3
18
1
Order By: Relevance
“…4 & 6A). This is contrary to work done by Whitten et al (2014), which showed greater bacterial diversity in diseased shell compared to healthy shell. These previous results, however, were based on methods that recovered an average of 8 to 11 taxa per sample.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…4 & 6A). This is contrary to work done by Whitten et al (2014), which showed greater bacterial diversity in diseased shell compared to healthy shell. These previous results, however, were based on methods that recovered an average of 8 to 11 taxa per sample.…”
Section: Discussioncontrasting
confidence: 99%
“…OTU 118 was most closely aligned with Arenicella chitinivorans (99% sequence identity), a bacterium that differs from others in the same genus by its ability to degrade chitin (Nedashkovskaya et al 2013). Given that previous work by Whitten et al (2014) also recovered members of this genus from lesioned areas of the lobster shell, it appears that the ability to degrade chitin may be an important characteristic allowing bacteria to thrive on both the affected and transitionary shell.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Significantly lower levels of 3‐(4‐hydroxyphenyl) lactate, which also showed a significant correlation with accumulated teflubenzuron levels, in the low‐ and high‐dose shrimps, further points to bacterial overgrowth in the teflubenzuron‐treated shrimps (Spaapen, Ketting, Wadman, Bruinvis, & Duran, ). The exposures may be causing dysregulation of normal and pathogenic/opportunistic bacteria in the P. montagui causing the skewing of the levels (Vogan, Powell, & Rowley, ; Whitten et al, ), as also indicated by the annotation of some of the significant DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of ESD is still debated within the scientific literature, but recent studies have suggested that the presence of Aquimarina sp. ‘homaria’ results in the exacerbation of lesions (24). Aquimarina sp.…”
Section: Genome Announcementmentioning
confidence: 99%